A sandwich finite element for the analysis of piezoelectric adaptive shells of revolution - Gorge, Valérie; Benjeddou, Ayech; Ohayon, Roger (European Journal of Computational Mechanics, 2002)
A simple finite element is proposed for the analysis of axisymmetric sandwich shells with piezoelectric faces. The latter are assumed through-thickness polarised and fully covered with electrodes on their inner and outer surfaces. Layerwise first-order shear deformation theory and displacement continuities at the sandwich interfaces are combined to reduce the mechanical unknowns to the faces mean and relative tangential displacements and bending rotations, augmented by the shell transverse deflection. Together with a layerwise linear electrical potential, these are first expanded with Fourier series along the shell circumference, then linearly interpolated along the meridian using Lagrange polynomials. Validation of the proposed piezoelectric sandwich conical finite element, through comparison with analytic free-vibration results available in the literature, has been found satisfactory.